Nutritional status and hemoglobin level in elementary schoolchildren - Marlina Jumrakh; Iskandar Z. Lubis; Noval Azis (Indonesian Pediatric Society, 2001)
A study was conducted in 1999 to determine nutritional status and hemoglobin level and their correlation among students in two primary schools in at Binjai, North Sumatra, Indonesia. Nutritional status was measured based on weight for age (W/A), height for age (H/A) and weight for height (W/H) according to NCHS criteria. Anemia was defined as hemoglobin level of less than 12 g/dl as measured with cyanmethemoglobin. Ninety-six children were available for analysis. We found that based on W/A, H/A and W/H, there were 23 (23%), 16 (17%), 11 (12%) of children suffered from protein energy malnutrition (PEM), respectively. There were 48 (50%) children with anemia. Children with PEM and anemia were 13 (59%), 9 (56%) and 9 (82%) respectively. In conclusion we found that not all of new students in those primary schools were healthy. There was correlation between anemia and PEM based on W/H measurement, but not when compared to W/A and H/A criteria.